BushenHuoxue Recipe for the Treatment of Prethrombotic State of ACA-Positive Recurrent Miscarriage via the Regulation of the PI3K-AKT Signaling Pathway. (14th February 2022) - Yang, Xuan; Su, Shulan; Ren, Qingling; Liu, Lijing; Li, Jiashang; Zhang, Wen; Cai, Ke; Xu, Zhuo; Pan, Xin
Abstract : Background . Although the Bushen Huoxue (BSHX) recipe is commonly used for the effective treatment of the prethrombotic state of recurrent abortions, its mechanism of action is unclear. In this article, we investigated the therapeutic effects of BSHX on anti-cardiolipin antibody (ACA) positive recurrent miscarriage mice and the molecular mechanism involved in the treatment of the prethrombotic state of ACA-positive recurrent miscarriages based on the PI3K-Akt signaling pathway, to provide a scientific basis for clinical practice. Methods . An ACA-positive recurrent miscarriage mouse model and normal pregnancy mouse model were adopted in this experiment. Seventy CBA/J female mice were induced to establish the ACA-positive recurrent model; the mice were mated with DBA/2 male mice. Of these mice, 50 became pregnant, which were randomly divided into a BSHX high-dose group (BH, 2.52 g/kg), BSHX medium-dose group (BM, 1.26 g/kg), BSHX low-dose group (BL, 0.63 g/kg), model group (M, distilled water), and an aspirin enteric-coated tablet group; each group had 10 mice. In addition, 16 CBA/J female mice were induced to establish the normal pregnant mouse model; the mice were mated with BALB/C male mice. Of these mice, 10 became pregnant, which were used as the blank control group (C) and received distilled water by gavage. Stillbirth and abortion rates were recorded for each group, and the uterine tissue, urine, and serum were collected. The serum expression levels of ACA, interleukin-6 (IL-6), progesterone, estradiol, and endometrial histological changes were compared between the groups. Metabolomics was performed on the urine and uterine tissues of both groups using UHPLC-QTOF/MS, and the expression levels of PI3K, p -PI3K, AKT, and p -AKT proteins in the uterine tissues were detected using Western blot. Results . Compared with the model pregnancy group, the BSHX high-dose group, BSHX medium-dose group, and BSHX low-dose group all had a lower absorption rate of mouse embryos, improved uterine histopathological morphology, significantly reduced serum levels of ACA and IL-6, increased serum levels of progesterone and estradiol, and significantly upregulated uterine levels of p -AKT, PI3K, and p -PI3K proteins. The metabolomic results showed that the metabolic levels in the urine and uterine tissues were significantly altered in the mouse model of ACA-positive recurrent abortion. The results also suggested that the pathogenesis of ACA-positive recurrent abortion may be associated with metabolic pathways, such as pentose, glucuronide, lysine degradation, and steroid hormone biosynthesis. Conclusion . The BSHX recipe improved the uterine histopathological morphology of pregnant mice and promoted vascular formation in uterine tissues. The mechanisms involved the reduction in serum ACA and IL-6 levels, the increment in serumprogesterone and estradiol levels, the upregulation of the levels of p -AKT, PI3K, and p -PI3K proteins, and the activation of the PI3K-Akt signaling pathway. These data will be useful for effective drug research and development.